Skeletal muscle vasodilatation at the onset of exercise - Clifford, Philip S (Blackwell Science Inc, 2007)
The mechanism for exercise hyperaemia is a century old enigma. Much of the research on the topic has focused on the factors controlling skeletal muscle blood flow during steady-state dynamic exercise. It is likely that the factors which initiate the increase in blood flow are distinct from those which sustain the elevated blood flow. There is now convincing evidence that there is rapid vasodilatation following release of muscle contraction. Metabolic, neural and acetylcholine spillover mechanisms do not appear to explain the initial dilatation. Heretofore there has been only circumstantial evidence regarding the role of potassium released by skeletal muscle fibres. Studies which interrupt potassium-mediated dilatation are just emerging and are not conclusive. In addition, the latency of the vascular smooth muscle response to potassium makes it desirable to identify a mechanism that does not rely on diffusion of a vasoactive agent. Compression of the intramuscular arterioles during contraction could activate a mechanosensitive response by the vascular smooth muscle and/or endothelium. Recent in vitro and in vivo data support the notion that brief periods of mechanical compression elicit rapid vasodilatation. Thus, vascular compression could represent a feedforward mechanism for initiating skeletal muscle vasodilatation at the onset of exercise.